PERAN MASJID SEBAGAI SENTRUM DAKWAH MAQOSID SYARIAH DAN RELASINYA DENGAN CIRCURAL ECONOMY - Ahmad Raziqi (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
The early history of the mosque was made simple and capable of being a magnet for Muslims to carry out worship, da'wah and the center of Islamic civilization. Including matters of muamalah which are in accordance with maqosid sharia and have a positive relationship to the circular economy. The number of mosques based on the 2018 SIMAS application has reached 242,823 mosques in Indonesia. This is enough to support optimizing the role of the mosque in order to achieve this mosque-based circular economy that requires critical efforts. If there is a mosque that wants to start preaching and implementing a mosque-based circular economy. This study uses qualitative research with the library study method. So that in this study finding history according to Hegel is the spirit that is conveyed as material for reflection and intelligence as explained that mosques are indeedas a place of worship, a place for consultation, economic affairs, social affairs, culture, education, social assistance, soldier or military training and the preparation of weapons, a place for treatment for war victims, a center for wisdom or information and a symbol of defending religion. WhereasMaqosiq Sharia relations and circular economy both have the goal of maintaining the continuity and adequacy of today's dharuriyat, hajiyat and tahsiniyat needs for future generations. Mosque management in this case certainly has to return to the spirit and reflection of history where the mosque was originally established at the time of the Prophet had a simple design and had complex functions of rubufundah and muamalah.